KREATIVITAS GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA DI SEKOLAH SMA ISLAM NUSANTARA MALANG - Muhammad Fajri Farouk; Azhar Haq; Moh Eko Nasrullah (VICRATINA, 2022)
Education is a basic human need in living life in the era of globalizationand is useful for developing self-potential. Education is an important partof the national development process. All school members who are involvedin character development are essentially an effort to build the characterof students. This student character building can be done by increasingdiscipline in the school environment. Students in participating in learningactivities at school cannot be separated from the rules and regulationsthat are required at their school. Every student is required to behave inaccordance with the rules and regulations in the school called studentdiscipline. While the rules, regulations and various other provisions thatregulate student behaviour are called school discipline. Teachers have avery important role in the application of student discipline in schools.Teachers are role models for students, teachers need to pay attention tothe needs or interests of students in instilling discipline. For example, astudent is late for school because he wakes up late because he stays uplate. So, by knowing the source of disciplinary disorders, you will also knowhow to overcome them In improving student discipline, it is necessary tohave teacher creativity as one of the supports for student discipline atschool. This study was conducted to determine the characteristics ofstudent discipline at SMA Islam Nusantara Malang and the creativity ofteachers in the formation of student discipline. The results showed that,(1) the level of discipline of students at SMA Islam Nusantara Malang isgood, this can be seen from the characteristics of discipline in matters oftime to enter school, follow the teaching and learning process, and havegood morals, and can follow the rules. in the school environment and gohome on time. The results showed that the student's level of discipline was95%. (2) the form of teacher creativity in student discipline is carried outwith various punishments or sanctions that are medical in nature.